2012
DOI: 10.1039/c1cy00299f
|View full text |Cite
|
Sign up to set email alerts
|

Modified zeolite ZSM-5 for the methanol to aromatics reaction

Abstract: Catalysts comprising zeolite ZSM-5 impregnated with precious metals including Ag, Cu, Ni, Pd, Ir and Ru, have been tested for the methanol to hydrocarbons reaction in a continuous flow fixed bed reactor. Comparison with the activity of unmodified ZSM-5 showed that Ag, Cu and Ni enhanced the selectivity to C 6 -C 11 aromatic products by a factor of two or higher. Moreover, Ag/ ZSM-5 showed improved selectivity for the C 6 -C 7 fraction of aromatic products. Ni/ZSM-5 was found to be selective to naphthalene, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
136
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(145 citation statements)
references
References 45 publications
4
136
0
Order By: Relevance
“…Conte et al have reported that in the methanol conversion, the selectivity to aromatic compounds was improved by loading metal species on ZSM-5 due to the interaction of acid sites of zeolite with basic sites of metal oxide [16]. The interaction of metal species with acid sites of zeolite involves changes in acid properties of the zeolite as well.…”
Section: Introductionmentioning
confidence: 99%
“…Conte et al have reported that in the methanol conversion, the selectivity to aromatic compounds was improved by loading metal species on ZSM-5 due to the interaction of acid sites of zeolite with basic sites of metal oxide [16]. The interaction of metal species with acid sites of zeolite involves changes in acid properties of the zeolite as well.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] Modification with Ag, Cu and Ni was found to enhance the selectivity of methanol to C6-C11 aromatic products. 23 It was reported that doping of HZSM-5 with Ni allows for an improvement of catalyst stability against coke formation in the transformation of bioethanol into olefins. 24 Incorporation of iron oxide nanoparticles (NPs) into zeolites was carried out for magnetic separation or magnetic stabilization, 25,26 to assist recrystallization of zeolites, 26 and for modification of catalytic properties.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to differences in ABs, the major difference between these catalysts is propylene selectivity; HZ produced more propylene (21%) than HZ-D (13%) and HZ-DA (14%) did. Propylene is a major precursor of ABs [45,46] and also a cracked product in arene and olefin cycles [36]; HZ-D is more active than HZ-DA in propylene aromatization to ABs because both catalysts possess great mesoporosities, but the former is enriched with non-framework Al. This difference is in accordance with the aforementioned hypothesis that non-framework Al species facilitate the hydride transfer and can promote aromatics yields.…”
Section: Resultsmentioning
confidence: 99%
“…Another point that should be addressed is the distributions of C 4 -C 7 hydrocarbons, which are generated together with ABs via the intermolecular hydrogen transfer of their precursors, i.e., olefins [45,46]. If the effect of side reactions is trivial, the selectivity of ABs should be positively correlated with that of C 4 -C 7 hydrocarbons.…”
Section: Resultsmentioning
confidence: 99%